Effect of Mycoplasma hominis and cytomegalovirus infection on pregnancy outcome: A prospective study of 200 Mongolian women and their newborns. - Byambaa Otgonjargala; Kathrin Becker; Gunchin Batbaatar; Sandag Tsogtsaikhan; Jamsranjav Enkhtsetseg; Altangerel Enkhjargal; Klaus Pfeffer; Ortwin Adams; Chimeddorj Battogtokh; Birgit Henrich (PLoS ONE, 2017)
In Mongolia, diagnostic tests for the detection of the sexually transmitted mycoplasmas, ureaplasmas, Herpes simplex virus (HSV), and cytomegalovirus (CMV) are currently not routinely used in clinical settings and the frequency of these STIs are enigmatic. The prevalence of these STI pathogens were prospectively evaluated among 200 Mongolian pregnant women and their newborns and correlated with pregnancy outcome. TaqMan PCRs were used to detect bacterial and viral STI pathogens in pre-birth vaginal swabs of the pregnant women and in oral swabs of their newborns. A standardized questionnaire concerning former and present pregnancies was developed and linear regression analysis was used to correlate pathogen detection with pregnancy outcome. Ureaplasmas were the most prevalent of the tested pathogens (positive in 90.5% positive women and 47.5% newborns), followed by mycoplasmas (32.5% and 7.5%), chlamydia (14.5% and 7.5%), trichomonas (8.5% and 4.0%) and gonococcus (0.5% and 0%). CMV was found in 46.5% of the pregnant women and in 10.5% of their newborns, whereas HSV-2 was detected in only two mothers. Multiple regression analyses indicate that colonization of the mothers with U. urealyticum, M. hominis, T. vaginalis or CMV is associated with transmission to newborns and that transmission of M. hominis or CMV from Mongolian pregnant women to offspring is associated with reduced neonatal length and gestational age. Thus, diagnostic tests for their detection should be implemented in the clinical settings in Mongolia.